2021
DOI: 10.1007/s00244-021-00888-2
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Water, Sediment and Fish with Residues of Pesticides Used in Cotton Production in Northern Benin

Abstract: In Northern Benin, insecticides are used for cotton production. These insecticides can be easily transferred to water ponds close to cotton elds. To monitor insecticides levels in water, sediments and sh samples from water ponds, a GC-MS analytical method was developed to detect residues of endosulfan, DDT and its parent compounds, isomers of HCH, pyrethroids and chlorpyrifos. In addition, the in uence of storage conditions of water sample on pesticides determination performance has been studied. The limits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Ba et al (2022) asserted with certainty that transboundary river pollution is an environmental concern on a global scale, as noted in their examination of pollution control legalities in the Niger River Basin. For instance, in the northern region of Benin, various insecticides employed in cotton cultivation have been found to pollute the Niger River's tributaries' water (Douny et al, 2021). It is essential to recognize that a river's water quality is influenced by factors such as the runoff from its catchment area, sewage discharge, and waste disposal.…”
Section: Resultsmentioning
confidence: 99%
“…Ba et al (2022) asserted with certainty that transboundary river pollution is an environmental concern on a global scale, as noted in their examination of pollution control legalities in the Niger River Basin. For instance, in the northern region of Benin, various insecticides employed in cotton cultivation have been found to pollute the Niger River's tributaries' water (Douny et al, 2021). It is essential to recognize that a river's water quality is influenced by factors such as the runoff from its catchment area, sewage discharge, and waste disposal.…”
Section: Resultsmentioning
confidence: 99%
“…The most used pesticides in northern Benin are endosulfan (a forbidden insecticide) and glyphosate (a herbicide) ( Dognon et al., 2018 ; Gouda et al., 2019 ; Adechian et al., 2015 ; Agbohessi et al., 2011 ). As some pesticide residues have been found in food consumed in Benin and West Africa, they might be present also in WG ( Douny et al., 2021 ; Ingenbleek et al., 2019 ; Dossou et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the volume of this toxicant used in cotton fields, this insecticide currently occupies a place of choice. Several studies had already revealed that, in the Benin cotton basin, the doses of pesticides recommended for the treatment of crops are not necessarily those practiced by farmers [1,10]. These growers increase the recommended amounts of pesticides at will [1].…”
Section: Experimental Designmentioning
confidence: 99%